2021
DOI: 10.1111/nph.17351
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and modulation of diterpenoid metabolism improves glandular trichome formation, artemisinin production and stress resilience in Artemisia annua

Abstract: Summary Plants synthesize diverse diterpenoids with numerous functions in organ development and stress resistance. However, the role of diterpenoids in glandular trichome (GT) development and GT‐localized biosynthesis in plants remains unknown. Here, the identification of 10 diterpene synthases (diTPSs) revealed the diversity of diterpenoid biosynthesis in Artemisia annua. Protein–protein interactions (PPIs) between AaKSL1 and AaCPS2 in the plastids highlighted their potential functions in modulating metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…For example, in trichomes that accumulate volatile compounds these may be stored in subcuticular spaces, as occurs in peppermint, or between the secretory cells as in tomato (Schuurink & Tissier, 2020). The metabolites accumulated in GTs typically have anti‐herbivory activity, making GTs an important part of plant defenses against biotic stress, but they also produce compounds with pharmaceutical applications such as the antimalarial artemisinin that accumulates in the GTs of Artemisia annua (Chen et al., 2021), meaning that their metabolism has also been studied with a view to genetic engineering (Huchelmann et al., 2017).…”
Section: Cell‐type‐specific Metabolic Phenotypesmentioning
confidence: 99%
“…For example, in trichomes that accumulate volatile compounds these may be stored in subcuticular spaces, as occurs in peppermint, or between the secretory cells as in tomato (Schuurink & Tissier, 2020). The metabolites accumulated in GTs typically have anti‐herbivory activity, making GTs an important part of plant defenses against biotic stress, but they also produce compounds with pharmaceutical applications such as the antimalarial artemisinin that accumulates in the GTs of Artemisia annua (Chen et al., 2021), meaning that their metabolism has also been studied with a view to genetic engineering (Huchelmann et al., 2017).…”
Section: Cell‐type‐specific Metabolic Phenotypesmentioning
confidence: 99%
“…GST structures are made up of 10 symmetric cells and are thought to be the main biofactories for artemisinin production, storage, and secretion, however, there is also a report on the production of artemisinin in the non-glandular trichomes of self-pollinated inbred A. annua ( Judd et al., 2019 ). The exclusive expression of artemisinin pathway key enzymes in GSTs, nominate them to be the true cell biofactories and the target for metabolic engineering and breeding strategies to improve their efficiency, such as by increasing their density ( Mutabingwa, 2005 ; Schilmiller et al., 2008 ; Chen et al., 2021 ). However, the lack of a model plant for GST study, as well as poor knowledge of the mechanism underlying their development, are two limiting constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of this plant, substantial research has been carried out to find ways of escalating the in planta artemisinin production, as its chemical synthesis is quite complex and costly. Exogenous application of several phytohormones has been found to enhance the terpenoid biosynthesis in many aromatic plants (Shukla et al 1992 ), and numerous studies have shown the impact of exogenous application of different phytohormones like salicylic acid (Pu et al 2009 ; Aftab et al 2011a ; Kumari et al 2018 ), gibberellic acid (Aftab et al 2010 ; Banyai et al 2011 ; Chen et al 2021 ), abscisic acid (Zehra et al 2020 ), and methyl jasmonate (Aftab et al 2011b ; Zhou and Memelink 2016 ) in artemisinin enhancement. Therefore, this study was carried out to investigate the impact of exogenous GR24 treatment on growth, physiology, and artemisinin biosynthesis in A. annua .…”
Section: Introductionmentioning
confidence: 99%